Proton-pump inhibitor use amongst patients with severe hypomagnesemia - Seah, Sherry; Tan, Yen Kheng; Teh, Kevin; Loh, Wann Jia; Tan, Pei Ting; Goh, Leng Chuan; Malakar, Roy Debajyoti; Aw, Tar Choon; Lau, Chin Shern; Dhalliwal, Trishpal; Kui, Swee Leng; Kam, Jia Wen; et al. (Frontiers in Pharmacology, 2023)
Introduction Long-term proton pump inhibitor (PPI) use has been associated with hypomagnesemia. It is unknown how frequently PPI use is implicated in patients with severe hypomagnesemia, and its clinical course or risk factors. Methods All patients with severe hypomagnesemia from 2013-2016 in a tertiary center were assessed for likelihood of PPI-related hypomagnesemia using Naranjo algorithm, and we described the clinical course. The clinical characteristics of each case of PPI-related severe hypomagnesemia was compared with three controls on long-term PPI without hypomagnesemia, to assess for risk factors of developing severe hypomagnesemia. Results Amongst 53,149 patients with serum magnesium measurements, 360 patients had severe hypomagnesemia (<0.4mmol/L). 189 of 360 (52.5%) patients had at least possible PPI-related hypomagnesemia (128 possible, 59 probable, two definite). 49 of 189 (24.7%) patients had no other etiology for hypomagnesemia. PPI therapy was stopped in 43 (22.8%) patients. Seventy (37.0%) patients had no indication for long-term PPI use. Hypomagnesemia resolved in most patients after supplementation, but recurrence was higher in patients who continued PPI, 69.7% versus 35.7%, P=0.009. On multivariate analysis, risk factors for hypomagnesemia were female gender (OR 1.73; 95% CI: 1.17–2.57), diabetes mellitus (OR, 4.62; 95% CI: 3.05–7.00), low BMI (OR, 0.90; 95% CI: 0.86–0.94), high-dose PPI (OR, 1.96; 95% CI: 1.29–2.98), renal impairment (OR, 3.85; 95% CI: 2.58–5.75), and diuretic use (OR, 1.68; 95% CI: 1.09–2.61) Conclusion In patients with severe hypomagnesemia, clinicians should consider the possibility of PPI-related hypomagnesemia and re-examine the indication for continued PPI use, or consider a lower dose.